Numerical Investigation on Free Vibration Analysis of Kevlar/Glass/Epoxy Resin Hybrid Composite Laminates - Quanjin, Ma; Merzuki, M.N.M.; Rejab, M.R.M.; M.S.M. Sani; Bo Zhang (Malaysian Journal on Composites Science and Manufacturing, 2022)
This paper investigates the free vibration analysis of kevlar/glass/epoxy resin hybrid composite laminates. The ABAQUS software is studied to obtain the natural frequency with different fiber hybridization effects. The 3D shell element models evaluate natural frequency and mode shape in the quasi-isotropic laminated composite. The numerical analysis results are studied and compared between ABAQUS and ANSYS software. It was shown that the natural frequency value between ABAQUS and ANSYS software provided almost the same value. The error value between ABAQUS and ANSYS ranged from 1.03 % to 2.30 %. It was found that the error between the experimental and numerical results was from 1.15 % to 13.51 %. It was concluded that the percentage error value was significantly dependent on the mesh size. Furthermore, the reasonable agreement between experimental and ANSYS results can better analyze the free vibration of composite laminates.